The Place of InvestmVents in the Activity of Commercial Banks and Its Improvement (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Annotation: The article examines the issues of improving the accounting and auditing of investments, taking into account the improvement of the financial condition of commercial banks. Based on this, financial indicators of commercial banks in Uzbekistan were analyzed and conclusions and proposals were formulated.